Serum Lipid Profile status of Type 2 Diabetic Patients in the cross section population in Dhaka City of Bangladesh (Bangladesh Journal of Medical Science, 2012)
Objectives: Serum lipid profile viz the level of total cholesterol (TC), Triglyceride (TG), HDL-cholesterol and LDL-cholesterol of type2 diabetic patients have been studied and compares them with levels of control subjects. Results: The mean value of the TG level for male diabetics was higher than that for the female diabetics and the mean values of TC, HDL-C and LDL-C were not found significantly different between male and female diabetics. Hyperlipidemia has a documented causative relation with CAD, but the major risk associated with diabetes may be due to the associated hyperlipidemia. The study revealed that dyslipidemia is very common in type2 diabetics and the most common abnormality observed was increased serum triglyceride levels (58%). The next common abnormality was decreased serum high-density lipoprotein cholesterol (HDL-C) levels and increased serum low-density lipoprotein cholesterol (LDL-C) levels. A high total serum cholesterol levels was found in 41% patients. 39% of the patients examined were overweight, and 7% were overtly obese. Conclusion: Thus, the study clearly shows the relationship between type2 diabetes and hyperlipidemia, which may influence the mechanism by which type2 diabetes is associated with increased CAD risk. DOI: http://dx.doi.org/10.3329/bjms.v11i2.11479 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 121-125